PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SATUAN POLISI PAMONG PRAJA KABUPATEN REMBANG - Hersusetyo, Ardhanang Abril; Dewi, Dian Ayu Liana (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
The aim of this research is to prove and analyze the influence of leadership, motivation and work discipline on the performance of Rembang Regency Civil Service Police Unit Civil Servants. This research uses the dependent variable employee performance and uses the independent variables leadership, motivation and work discipline. The population used in the research carried out were all Civil Servants of the Rembang Regency Civil Service Police Unit, a total of 69 people. The sampling method in the research carried out was a saturated sample (census), the sample in the research carried out was the entire population or all Civil Servants of the Civil Service Police Unit, totaling 69 people. The analysis technique used is multiple linear regression analysis. The research results show that the leadership variable has a positive and insignificant effect on employee performance, the motivation variable has an insignificant negative effect on employee performance and the work discipline variable has a significant positive effect on employee performance. From the determination test, it is known that the R Square adjuster coefficient is 0.177, so it can be interpreted that the variables of leadership, motivation and work discipline can explain 17.7% of employee performance, while the remaining 82.3% of employee performance is influenced or explained outside of this research model.